PERBANDINGAN KEMAMPUAN PENGUASAAN VOCABULARY MENGGUNAKAN MODEL TOTAL PHYSICAL RESPONSE (TPR) DAN VISUAL AUDITORY KINESTHETIC (VAK) PADA SISWA KELAS V SDIT IBNU ABBAS CIKARANG - Azzahra, Dinda; Rikmasari, Rima (Universitas Islam 45 Bekasi, 2025)
This research is motivated by the tendency of teachers who still use a teacher centered approach and rarely apply varied learning so that it affects student learning activities to be passive. This study aims to determine the comparison of the TPR model and the VAK model in class V SDIT Ibnu Abbas Cikarang. The method used in this research is experimental. This study used experimental classes I and II in which experimental class I was treated with the TPR model and experimental class II using the VAK model. The results of this study are: The vocabulary mastery ability of grade V students using the TPR model in experimental class I has an average of 81.82. Where the average result before learning was 73.86. So that there is an increase in average results by 7.96. The ability to master the vocabulary of Abbas by using the VAK model in experimental class II shows the average result is 87.54. Where the average obtained before the learning is 75.11. So that there is an increase in average results by 12.43. The t-test analysis obtained a 2 tailed significance value of 0.036 < with a significant level of 0.05, thenHo is rejected and Hi is accepted. This means that there is a significant difference in vocabulary mastery ability between using the total physical response (TPR) and visual auditory kinesthetic (VAK) models for fifth grade students of SDIT Ibnu Abbas Cikarang.